2014
DOI: 10.2527/jas.2014-7887
|View full text |Cite
|
Sign up to set email alerts
|

Pain sensitivity and healing of hot-iron cattle brands1

Abstract: Hot-iron branding is painful for cattle, but little is known about the duration of or effective methods to control this pain. This work quantified pain sensitivity and healing in branded and unbranded animals. In addition, the effects of a single injection of nonsteroidal anti-inflammatory drug (NSAID) were also considered; this has been suggested as practical method of mitigating pain in the hours after the procedure. Calves (mean±SE, 126±2.2 d and 112±2.8 kg) were hot-iron branded and allocated to 1 of 4 tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 21 publications
3
41
1
Order By: Relevance
“…When the evaluation extended beyond 7 d, Molony et al (1995) and Marti et al (2017a) did not find changes in lying time in 1 wk and 2-mo-old calves compared with noncastrated calves. Furthermore, Tucker et al (2014b) reported that the time branded calves spent lying was not different from nonbranded calves. Note: NM, single s.c. injection of lactated ring at castration time; M, single injection of s.c. meloxicam (0.5 mg kg −1 ) at castration time; Med, medication effect; n, number of animals observed at each score; Median, median days to reach each healing score relative to days of castration and castration and branding; FCL, 95% confidence limits distribution free of the days to reach each healing score.…”
Section: Itemsmentioning
confidence: 99%
See 4 more Smart Citations
“…When the evaluation extended beyond 7 d, Molony et al (1995) and Marti et al (2017a) did not find changes in lying time in 1 wk and 2-mo-old calves compared with noncastrated calves. Furthermore, Tucker et al (2014b) reported that the time branded calves spent lying was not different from nonbranded calves. Note: NM, single s.c. injection of lactated ring at castration time; M, single injection of s.c. meloxicam (0.5 mg kg −1 ) at castration time; Med, medication effect; n, number of animals observed at each score; Median, median days to reach each healing score relative to days of castration and castration and branding; FCL, 95% confidence limits distribution free of the days to reach each healing score.…”
Section: Itemsmentioning
confidence: 99%
“…However, it was expected that the combination of castration and branding would increase the deposition of cortisol within the hair. This hypothesis was based on the findings of Tucker et al (2014aTucker et al ( , 2014b who reported greater pain sensitivity values (g force) in hot-iron-branded calves using a Von Frey anesthesiometer applied to the brand site for at least 10 wk after the procedure. However, as discussed previously, pain sensitivity of the brand site might not be sufficiently intense to result in increased hair cortisol concentrations, or pain sensitivity may be poorly correlated with other indicators of stress and (or) pain.…”
Section: Itemsmentioning
confidence: 99%
See 3 more Smart Citations